2018
DOI: 10.1016/j.jeurceramsoc.2018.04.060
|View full text |Cite
|
Sign up to set email alerts
|

Damage microstructure evolution of helium ion irradiated SiC under fusion relevant temperatures

Abstract: In-situ transmission electron microscopy (TEM) with ion irradiation has been used to study the damage microstructure evolution of He ion irradiated 4-H SiC at nuclear fusion relevant temperatures. The SiC samples were irradiated with 20 keV He ions at 25, 400, 800 and 1200°C to a dose of 5.0 displacements per atom (DPA). At 25°C, the material fully amorphises at 1.5 DPA and no He bubble nucleation occurs up to the doses studied. At 400 and 800°C, He bubble nucleation occurs and the material remains crystalline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 56 publications
(90 reference statements)
1
12
0
Order By: Relevance
“…It is especially the case for high dose rates of incoming helium atoms combined with a restricted vacancy supply. In silicon carbide, several studies reported observations of helium-filled bubbles and platelets [4][5][6][7][8][9][10][11][12]. Such highly pressurized defects can significantly degrade the structural integrity of the host, a particularly annoying feature for a structural or confining material.…”
Section: Introductionmentioning
confidence: 99%
“…It is especially the case for high dose rates of incoming helium atoms combined with a restricted vacancy supply. In silicon carbide, several studies reported observations of helium-filled bubbles and platelets [4][5][6][7][8][9][10][11][12]. Such highly pressurized defects can significantly degrade the structural integrity of the host, a particularly annoying feature for a structural or confining material.…”
Section: Introductionmentioning
confidence: 99%
“…Closely related to the current work, He irradiation has been studied and reported to induce amorphisation in single crystalline SiC. Liu et al [48] using 70 keV He ions and Leclerc et al [14] using 50 keV He ions at room temperature reported amorphisation critical doses of 1.1 dpa and 1.3 dpa, respectively, whilst Harrison et al [26] under identical energy and temperature conditions. These observations indicate a better resistance of the NWs to amorphisation as compared to the foils at room temperature.…”
Section: Changes In Sic Microstructure Induced By Room Temperature Irmentioning
confidence: 70%
“…The foils were prepared from 4H-SiC wafers obtained from Cree Corporation, USA (Product code: W4NPE4C-Y200). Using an ultrasonic disc cutter, the wafer was cut into 3 mm discs which were mechanically polished to ⁓100 μm and dimpled to ⁓50 µm then ion-beam milled using a precision ion polishing system (PIPS) to a thickness range of 50-70 nm as described previously [26]. All the samples used were 4H-SiC with 99.9% purity.…”
Section: Methodsmentioning
confidence: 99%
“…The presence of bubbles is indeed only detected at 550°C. In the absence of mobile vacancies [5,30], this should result from the thermally activated detrapping of He atoms from small He-V complexes that migrate to larger and more stable complexes leading to faster nucleation and growth of visible bubbles at elevated temperature [56]. A thermally enhanced mechanism of trap mutation or loop punching could also contribute to this observation.…”
Section: Enhancement Of Damagementioning
confidence: 99%